Investigation of coated and uncoated carbide cutting tool wear in dry turning of en aw 2007 aluminum alloy - Leksycki, Kamil; Patil, Gauravkumar Himmatrao; Małecka, Joanna; Cagan, Cinar Suleyman; Dąbrowski, Karol (Zielona Góra: Uniwersytet Zielonogórski)
The automotive, aerospace and marine industries make extensive use of aluminum and its alloys to produce a wide variety of components. This prompts research work related to improving manufacturing processes using these materials. One of the main problems in this area is the durability of cutting tools.
Keywords: tool wear; coated and uncoated inserts; dry turning; EN AW 2007 aluminum alloy